Orí O! A ideia de Pessoa, a Problemática do Destino e o Ritual do Bọrí entre os Yorùbás e no Candomblé (Orí O! The Idea of Person, the Problematic of Destiny and the Ritual of Bọrí among the Yorùbá and in Candomblé) - DOI 10.5752/P.2175-5841.2013v11n29p70 - Dias, João Ferreira (HORIZONTE - Revista de Estudos de Teologia e Ciências da Religião, 2013)
O presente artigo pretende analisar a ideia de pessoa entre os yorùbás da África Ocidental, a partir da conceção de orí, i. e., a cabeça, entendida entre eles como portadora de personalidade e destino, ideia amplamente difundida pela literatura sobre a matéria da personalidade humana e sentidos de destino. A partir do orí, adentrar-se-á pela problemática da predestinação entre os yorùbás e o sentido do ritual de alimento à cabeça, o bọrí, entre os yorùbás, com referência aos afro-brasileiros do Candomblé. A problematização conduzir-nos-á à constatação da pluralidade interpretativa do objeto, ao mesmo tempo que nos deixará diante da questão linguística da tradução dos conceitos, facto que influi na própria construção teológica. Ao mesmo tempo estaremos diante da construção histórica da religião yorùbá, notoriamente uma religião dinâmica e mutável que se fabrica nos diálogos com o cristianismo e islamismo. Processos de transformação que, aliás, são transponíveis para o Brasil, onde a celebração do orí se apresenta de modo diferenciado face à realidade autóctone africana. Palavras-chave: Yorùbás. Concepção de pessoa. Orí. Predestinação. Bọrí. Abstract The present paper aims to analyze the idea of person among the Yorùbá people of Western Africa, taking into account the conception of orí, i.e., the head, which is understood by them as the bowl of human personality and destiny. Those ideas are clearly present in the plural literature concerning the human personality and its destination among the Yorùbá people. Taking the orí as starting point, I shall problematize the predestination idea among the Yorùbá and the meaning of the bọrí, the ritual presented as ‘feeding-the-head’. Such process will be extended to Afro-Brazilian religious system named Candomblé. The problematization will guide my observation to the dramatic plurality of interpretations concerning destiny, while it will spell out the linguistic dilemmas around the translation of concepts. Those dilemmas influence, clearly, the theological construction of the object. At the same time, the paper will deliver us to the evidence of the historical construction of Yorùbá religion, which is a mutable and dynamic religious expression, highly crossed with Christianity and Islam (in African contexts). Those processes of transformation are also clear in Brazil, where the celebration of orí has different religious attitudes comparing to African native ones. Keywords: Yorùbá. Idea of person. Orí. Predestination. Bọrí.